Novel Class-AB Operational Amplifier for Compact and Energy-Efficient Wake-Up Sensor Systems - Hussam AlShammary (Sensors)
This paper presents a novel rail-to-rail Class-AB operational amplifier tailored for wake-up systems in motion sensor applications. By addressing limitations in free Class-AB designs, such as large inrush current, unstable bias conditions, and area ineffiiency, the proposed design achieves a gain of 59 dB and unity gain frequency of 550 kHz driving a 5 pF load. The inrush current is reduced from 1 mA to 7 µA, increasing the battery life. The layout area is reduced by 53% compared to the free Class-AB design, making it highly suitable for compact implementations. Operating at a low power consumption of 2 µW with a 1.8 V supply, the amplifier achieves a Signal-to-Noise-and-Distortion Ratio (SNDR) of 22 dB. These advancements demonstrate the potential of the design for energy-efficient analog front-end solutions in IoT and portable systems.